Nitrogen fixation responds to soil nitrogen at low but not high light in two invasive understory species. (6th February 2023) - Schmidt, Colleen B.; Funk, Jennifer L.; Wolf, Amelia A.; Akana, Palani R.; Palmer, Matthew I.; Menge, Duncan N. L.
Abstract: Light and soil nitrogen availability can be strong controls of plant nitrogen (N) fixation, but data on how understory N‐fixing plants respond to these drivers are limited despite their important role in ecosystem N cycling. Furthermore, ecosystem N cycling can be altered by the introduction of species with nutrient use patterns that differ from natives. We assessed how N fixation of two exotic, understory species responded to varying light and soil N environments. We sampled leaf tissue from Mimosa pudica L., Desmodium triflorum (L.) DC., and a nonfixing reference plant ( Axonopus ) growing in control and two N fertilization treatments under either N‐fixing or non‐N‐fixing trees, which may alter local soil nutrient cycling, across a range of light conditions. We measured N fixation with 15 N isotope dilution, and ensured that N‐fixing neighbour trees were in fact fixing N. All understory plants were wild‐growing species not native to the study location. Desmodium and Mimosa acquired 82.6% and 71.6% of their nitrogen from fixation (%Ndfa ) in the control, compared to 66.8% and 58.1% in the +10 g N m −2  year −1 treatment and 73.1% and 64.7% in the +15 g N m −2  year −1 treatment. These subtle %Ndfa differences across fertilization treatments were more apparent at low light availability and disappeared at high light availability. The amount of N fixed by neighbouring trees did not influence %Ndfa in the understory species. Synthesis . Our study shows some differences in N fixation across different nutrient environments at low light for two N‐fixing species, though the changes were small, and both species derived most of their N from fixation. These findings imply that introduced N‐fixing species could exacerbate ecosystem N enrichment, particularly under high soil N conditions. Abstract : Our study shows some differences in N fixation across different nutrient environments at low light for two N‐fixing species, though the changes were small, and both species derived most of their N from fixation. These findings imply that introduced N‐fixing species could exacerbate ecosystem N enrichment, particularly under high soil N conditions.